The Improvement of Communication and Mathematical Disposition Abilities through Discovery Learning Model in Junior High School - Dina, Zinatun Hayati; Ikhsan, M; Hajidin, Hajidin (JRAMathEdu (Journal of Research and Advances in Mathematics Education), 2019)
The purpose of this study was to determine the improvement of students' mathematical communication and disposition abilities taught with discovery learning models. This study us quantitative approach with the type of experimental research and the research design us pretest and posttest design type experiments. The sample was chosen randomly from two classes of 7th grade in one of public junior high school in Sigli, Aceh. The research instrument used was mathematical communication ability test and mathematical disposition questionnaire. The data analysis of students' communication and disposition ability was done by two-way ANAVA test at a significant level of 0.05. The results showed that the improvement of students' mathematical communication and disposition skills taught with discovery learning models was better than those taught with conventional approaches. Furthermore, there was no interaction between discovery learning model and the level of students towards improving communication skills and mathematical dispositions. Therefore, the mathematics teachers can implement discovery learning models in learning to build the next polyhedron. Future researchers should conduct research at other schools in order to improve students' mathematical communication skills in mathematics learning